Civilistic Public Order in the Context of Armenian NationMaturemen - Simonyan , T. (Bulletin of Yerevan University C: Jurisprudence, 2018)
While discussing V. Nersesianz`sCivilisticManifesto in the framework of the Armenian reality of XXI century, one can emphasize the importance of the civilizational maturement of a nation. This is very important, because there can be no approximation of a theory or even a social order to a nation’s existential reality, it they have no lines of convergence. This paper brings to light the possibility of matching the Armenian social reality to that of drafted in the CivilisticManifesto taking into account the civilizational maturement of the Armenian nation
Keywords: civilizational maturement, civilian property, socialist property, social consciousness, public demand, Civilistic Manifesto